Learning from conceptual models – a study of the emergence of cooperation towards resource protection in a social–ecological system - S. Harati-Asl; L. Perez; R. Molowny-Horas (Geoscientific Model Development)
Engaging ecological resource users in intervention to protect resources is challenging for governments due to the self-interest of users and uncertainty about intervention consequences. Focusing on a case of forest insect infestations, we addressed questions of resource protection and environmentally responsible behavior promotion with a conceptual model. We coupled a forest infestation model with a social model in which a governing agent applies a mechanism for the recognition and promotion of environmentally responsible behavior among several user agents. We ran the coupled model in various scenarios with a reinforcement-learning algorithm for the governing agent as well as best-case, worst-case, and random baselines. Results showed that a proper recognition policy facilitates emergence of environmentally responsible behavior. However, ecosystem health may deteriorate due to temporal differences between the social and ecological systems. Our work shows it is possible to gain insight about complexities of social–ecological systems with conceptual models through scenario analysis.